Student connectivity as an element of their learning ecosystem during the pandemic: Case study Universidad Pedagógica Veracruzana (Revista Innova Educación, 2022)
The present investigation allowed us to know the internet connectivity of the 3035 students of the Bachelor of Basic Education at the Universidad Pedagógica Veracruzana during the pandemic through a virtual survey carried out in the second semester of the 2020-2021 school year to all regional centers to identify the availability of this service by region, semester, sex and age range. The study was justified by the relevance of the university's public policies to continue distance academic activities during confinement during their teacher training. A quantitative approach was used with a descriptive, non-experimental scope. The levels of analysis of the information collected in the survey at the state level were limited to the Internet connection that existed in the community where the students were; the internet service they had at home; and the computer equipment with which they carried out their school activities. The results obtained allowed us to know that most of the students had an internet connection in their community and at home to carry out their school activities during confinement, facing teaching trends through learning ecosystems to achieve Education 4.0; Almost half of all of them had their own desktop or laptop computer, but a similar percentage worked with their cell phones, and the rest carried out their tasks with a borrowed device. It is concluded that, in general, the digital ecosystem of LEB students was characterized by having basic elements for their initial distance teaching training during the pandemic. However, technological and teaching support opportunities were pointed out that would offer them improvements in the said ecosystem and environment during their school career.
Keywords: diversification of education; learning ecosystem; teacher training; ICT